The Dual Role of miR-186 in Cancers: Oncomir Battling With Tumor Suppressor miRNA - Xiang, Ying; Tian, Qing; Guan, Li; Niu, Shuai-shuai (Frontiers in Oncology, 2020)
MicroRNAs (miRNAs) are a class of small non-coding RNAs which regulate gene expression at post-transcriptional level. Alterations of miR-186 expression were demonstrated in numerous cancers, shown to play a vital role in oncogenesis, invasion, metastasis, apoptosis, and drug resistance. MiR-186 was documented as a tumor suppressor miRNA in the majority of studies, while conflicting reports verified miR-186 as an oncomir. The contradictory role in cancers may impede the application of miR-186, as well as other dual-functional miRNAs, as a diagnostic and therapeutic target. This review emphasizes the alterations and functions of miR-186 in cancers and discusses the mechanisms behind the contradictory findings. Among these, target abundance and dose-dependent effects of miR-186 are highlighted. The paper aims to review the challenges involved in developing diagnostic and therapeutic strategies for cancer treatment based on dual-functional miRNAs.